Changes in fatty acid composition in the giant clam Tridacna maxima in response to thermal stress - Dubousquet, Vaimiti (Biol Open, 2016)
Temperature can modify membrane fluidity and thus affects cellular functions and physiological activities. This study examines lipid remodelling in the marine symbiotic organism, Tridacna maxima, during a time series of induced thermal stress, with an emphasis on the morphology of their symbiont Symbiodinium. First, we show that the French Polynesian giant clams harbour an important proportion of saturated fatty acids (SFA), which reflects their tropical location. Second, in contrast to most marine organisms, the total lipid content in giant clams remained constant under stress, though some changes in their composition were shown. Third, the stress-induced changes in fatty acid (FA) diversity were accompanied by an upregulation of genes involved in lipids and ROS pathways. Finally, our microscopic analysis revealed that for the giant clam's symbiont, Symbiodinium, thermal stress led to two sequential cell death processes. Our data suggests that the degradation of Symbiodinium cells could provide an additional source of energy to T. maxima in response to heat stress.